Media relations in an evolving media landscape - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2014)
Purpose – The purpose of this paper is to test the viability of the media relations framework, Mediating the Media model (Pang, 2010), and ascertains its relevance to practitioners in a changing media landscape in Singapore where social media is emerging as an alternative source of information tool. Design/methodology/approach – In-depth interviews with 20 media relations practitioners who were former journalists. Practitioners with journalism experience were chosen as they perform better at media relations (Sallot and Johnson, 2006a; Sinaga and Callison, 2008). Findings – The model posits two sets of influences, i.e. internal (journalist mindset, journalist routines and newsroom routines) and external (extra-media forces and media ideology) in media relations. Internal influences were found to be more prevalent than external influences and journalist mindset was the most pervasive factor influencing media relations. Research limitations/implications – Findings are based solely on interviews and some claims cannot be corroborated. As this is a qualitative study situated in one country, it is also not generalizable. Practical implications – This study will serve useful insights for new practitioners to approach media relations in a holistic and systematic manner and for seasoned practitioners to re-evaluate their current media strategies. Originality/value – This inaugural test found rigor in the model, and affords an in-depth understanding of the dynamics of journalist-practitioner relationships in a changing media landscape. It also presents an intriguing opportunity for the model to be applied to countries where the media industry operates under vastly different environments so as to ensure that the model stands up to scrutiny as it seeks to be positioned as a viable model for media relations.